Cardiac output in hyperoxia, normoxia, and hypoxia - Peltonen, J. E.; Tikkanen, H. O.; Rusko, H. K. (Medicine & Science in Sports & Exercise, 1999)
Male endurance athletes were measure at rest and during progressive cycling in hyperoxia (30% O2), normoxia (21% O2), and hypoxia (15% O2). Starting at 0 W, power was increased 100 W in 5-minute increments in the exercise task. Maximal cardiac output, VO2max, and maximal performance were diminished in hypoxia. Diminished COmax in hypoxia was affected both by decreased maximal stroke volume and heart rate. In hyperoxia, COmax was increased only slightly despite a correspondingly greater increase in VO2max. Implication: Changes in oxygen saturation in the atmosphere are only partially related to observed changes in parameters associated with cardiac output. (Medicine and Science in Sports and Exercise, 31(5), upplement abstract 816.)